Medical Swimming Cellbots. Issue 10 (6th October 2022) - Zhang, Hongyue; Li, Zesheng; He, Qiang
Abstract : Cell Robots Swimming cellbots based on living cells and synthetic components are able to realize self‐propulsion and self‐navigation in the body, which may overcome different biological barriers, sense and target the diseased sites autonomously. These biohybrid swimming cellbots can provide a revolutionary solution for precision medicine such as active target delivery, artificial insemination treatment of atherosclerosis, toxin clear, microsurgery. More details can be found in article number 2200094 by Qiang He and co‐workers.